Non-invasive MRI of blood-cerebrospinal fluid-barrier function in a mouse model of Alzheimer’s disease: a potential biomarker of early pathology - Charith Perera; Renata Cruz; Noam Shemesh; Tânia Carvalho; David L. Thomas; Jack Wells; Andrada Ianuș (Fluids and Barriers of the CNS)
Abstract Background Choroid plexus (CP) or blood-cerebrospinal fluid-barrier (BCSFB) is a unique functional tissue which lines the brain’s fluid-filled ventricles, with a crucial role in CSF production and clearance. BCSFB dysfunction is thought to contribute to toxic protein build-up in neurodegenerative disorders, including Alzheimer’s disease (AD). However, the dynamics of this process remain unknown, mainly due to the paucity of in-vivo methods for assessing CP function. Methods We harness recent developments in Arterial Spin Labelling MRI to measure water delivery across the BCSFB as a proxy for CP function, as well as cerebral blood flow (CBF), at different stages of AD in the widely used triple transgenic mouse model (3xTg), with ages between 8 and 32 weeks. We further compared the MRI results with Y-maze behaviour testing, and histologically validated the expected pathological changes, which recapitulate both amyloid and tau deposition. Results Total BCSFB-mediated water delivery is significantly higher in 3xTg mice (> 50%) from 8 weeks (preclinical stage), an increase which is not explained by differences in ventricular volumes, while tissue parameters such as CBF and T1 are not different between groups at all ages. Behaviour differences between the groups were observed starting at 20 weeks, especially in terms of locomotion, with 3xTg animals showing a significantly smaller number of arm entries in the Y-maze. Conclusions Our work strongly suggests the involvement of CP in the early stages of AD, before the onset of symptoms and behavioural changes, providing a potential biomarker of pathology.